2011
DOI: 10.2310/8000.2011.110334
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing performance measurement for emergency department care: consensus on evidencebased quality of care indicators

Abstract: Background: The evaluation of emergency department (ED) quality of care is hampered by the absence of consensus on appropriate measures. We sought to develop a consensus on a prioritized and parsimonious set of evidence-based quality of care indicators for EDs. Methods: The process was led by a nationally representative steering committee and expert panel (representatives from hospital administration, emergency medicine, health information, government, and provincial quality councils). A comprehensive review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 16 publications
2
108
0
3
Order By: Relevance
“…Our results are consistent with those of Schull and colleagues, 14 whose feasibility assessment in urban centres showed that 13 (27%) of 48 quality-of-care indicators could be measured with the use of current data elements in the Canadian Institute for Health Information's National Ambulatory Care Reporting System (NACRS) or the NACRS plus linkage with other administrative databases such as the Discharge Abstracts Database or death records. The 13 indicators did, however, include some higher-priority indicator categories for emergency department operations, such as patient safety and sepsis/infection.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are consistent with those of Schull and colleagues, 14 whose feasibility assessment in urban centres showed that 13 (27%) of 48 quality-of-care indicators could be measured with the use of current data elements in the Canadian Institute for Health Information's National Ambulatory Care Reporting System (NACRS) or the NACRS plus linkage with other administrative databases such as the Discharge Abstracts Database or death records. The 13 indicators did, however, include some higher-priority indicator categories for emergency department operations, such as patient safety and sepsis/infection.…”
Section: Discussionsupporting
confidence: 82%
“…Second, collection of data on certain priority indicators could be difficult in rural establishments owing to lack of resources. 14 The primary objective of this study was to investigate the feasibility of measuring the quality-of-care indicators defined by Schull and colleagues 12 in rural emergency departments in Quebec and to identify potential barriers to implementing the indicators. The study is a substudy of a larger cross-sectional multicentre research project 4,15 ( Figure 1).…”
mentioning
confidence: 99%
“…Consensus is still lacking on which measures are considered to be most accurate, extensive, clearly defined, and based on evidence 20,21 . Working towards a consensus of performance measures that reflect the general performance of an ED and whether or not certain quality improvement initiatives prove efficient is clearly warranted.…”
Section: Review Of Literaturementioning
confidence: 99%
“…6,11 De acordo com os critérios de qualidade, esta deveria ser inferior a 5% e o mais próxi-mo possível de 1%. 12,13 Na Unidade de Urgência Pediátrica (UUP) do Hospital de São Bernardo, o sistema de triagem classifica o doente numa de três categorias identificadas por uma cor e tempo alvo médio até à primeira observação médica. A primeira categoria corresponde à primeira prioridade, cor vermelha, atendimento imediato ou muito urgente (0 a 10 minutos).…”
unclassified